Genetic Diversity of Simulium damnosum complex Onchocerciasis Vector and its Influence on Entomological Monitoring in the West of Côte d'Ivoire - Siriki Simaro; Mathurin Koffi; Mahama Toure; Bernardin Ahouty; Ibrahim Konate; Abiba Sanogo Tidou (European Scientific Journal, ESJ, 2019)
In West Africa, Onchocerca volvulus, the causative pathogen of human onchocerciasis, is transmitted by sibling species of the Simulium damnosum complex. Little is known about blackfly intraspecific variability and its consequences on vectorial capacity in Côte d’Ivoire. This study reports the use of microsatellite markers to study the genetic profile and evaluate the gene flow between populations of S. damnosum s.l from three (3) different epidemiological facies in western Côte d’Ivoire, fifteen years after the end of onchocerciasis control program. Adult flies were collected on human attractants from 07 : 00 to 18 : 00 hours for three consecutive days by site, from December 2016 to October 2017. Four (4) microsatellite loci were used to characterize individuals from these populations. The four (4) loci were polymorphic with 13.25 alleles per locus. Two (2) specific alleles (190 bp and 290 bp), were reveal abundant with respective frequencies of 0.46 % and 0.58 %. Asignificant heterozygosity deficiency and low genetic differentiation (FST = 0.046, P = 0.024) have been observed for all the populations. The genetic analysis showed significant deviation from Hardy-Weinberg and significant heterozygosity deficiencies. Then, the great interspecific variability would be a general characteristic in S. damnosum s.l. At last, a probable evolution of the invasive strains of S. damnosum would have occurred in these localities. This study has shown significant deviation from Hardy-Weinberg and significant heterozygosity deficiencies in the populations of the three localities. The loci give independent estimate genetic parameters. The H3-4 locus to a low genetic differentiation between the populations.